BILINGUALS’ LINGUISTIC REPERTOIRE AND FOREIGN LANGUAGE INSTRUCTION: WHAT DO TEACHERS SAY ABOUT TEACHING EFL THROUGH TRANSLANGUAGING? - Gede Eka Putrawan; Tuntun Sinaga (Universitas Islam Sumatera Utara, 2022)
In recent decades, translanguaging has made rapid progress in the field of language instruction. The term